Poligami di Indonesia: Perbandingan Pemikiran Tekstual Hafidin dan Kontekstual Progresif Husein Muhammad - Aminatur Rosidah; Muhammad Haris Abdul Hakim (Institut Agama Islam Negeri (IAIN) Kediri, 2025)
Polygamy remains a sensitive issue in Indonesian society, particularly concerning gender justice and women’s protection. The differing perspectives of contemporary Muslim scholars such as Hafidin and Husein Muhammad reflect the dialectics of Islamic family law thought worth examining. This study employs normative legal research with a conceptual approach. Data were collected through a literature review of the Qur’an, hadith, Indonesia’s Marriage Law No. 1 of 1974, the Compilation of Islamic Law (KHI), and academic works discussing Hafidin and Husein Muhammad’s views. Hafidin interprets polygamy in a textualist-patriarchal manner, emphasizing outward justice such as rotation and financial support, while upholding male authority as absolute. Conversely, Husein Muhammad adopts a contextual-progressive approach that incorporates maqāṣid al-sharī‘ah, psychological aspects, and social impacts, thereby supporting stricter regulation by the state. Husein Muhammad’s perspective is more relevant in the modern context as it emphasizes substantive justice and protection for women. This highlights the importance of progressive approaches in Islamic family law to build families based on sakīnah, mawaddah, and raḥmah.